Identification of New World Quails Susceptible to Infection with Avian Leukosis Virus Subgroup J - Plachý, Jiří; Reinišová, Markéta; Kučerová, Dana; Šenigl, Filip; Stepanets, Volodymyr; Hron, Tomáš; Trejbalová, Kateřina; Elleder, Daniel; Hejnar, Jiří (Journal of virology, 2017)
UNLABELLED: The J subgroup of avian leukosis virus (ALV-J) infects domestic chickens, jungle fowl, and turkeys. This virus enters the host cell through a receptor encoded by the tvj locus and identified as Na+/H+ exchanger 1. The resistance to avian leukosis virus subgroup J in a great majority of galliform species has been explained by deletions or substitutions of the critical tryptophan 38 in the first extracellular loop of Na+/H+ exchanger 1. Because there are concerns of transspecies virus transmission, we studied natural polymorphisms and susceptibility/resistance in wild galliforms and found the presence of tryptophan 38 in four species of New World quails. The embryo fibroblasts of New World quails are susceptible to infection with avian leukosis virus subgroup J, and the cloned Na+/H+ exchanger 1 confers susceptibility on the otherwise resistant host. New World quails are also susceptible to new avian leukosis virus subgroup J variants but resistant to subgroups A and B and weakly susceptible to subgroups C and D of avian sarcoma/leukosis virus due to obvious defects of the respective receptors. Our results suggest that the avian leukosis virus subgroup J could be transmitted to New World quails and establish a natural reservoir of circulating virus with a potential for further evolution. IMPORTANCE: Since its spread in broiler chickens in China and Southeast Asia in 2000, ALV-J remains a major enzootic challenge for the poultry industry. Although the virus diversifies rapidly in the poultry, its spillover and circulation in wild bird species has been prevented by the resistance of most species to ALV-J. It is, nevertheless, important to understand the evolution of the virus and its potential host range in wild birds. Because resistance to avian retroviruses is due particularly to receptor incompatibility, we studied Na+/H+ exchanger 1, the receptor for ALV-J. In New World quails, we found a receptor compatible with virus entry, and we confirmed the susceptibilities of four New World quail species in vitro We propose that a prospective molecular epidemiology study be conducted to identify species with the potential to become reservoirs for ALV-J.
Keywords: Genetic Loci; aminokyseliny; exprese genu; Gene Expression; Host-Pathogen Interactions; retroviral receptor; Na+/H+ exchanger; genetické lokusy; virus ptačí leukózy; interakční proteinové domény a motivy; replikace viru; odolnost vůči nemocem; polymorfismus genetický; fylogeneze; Phylogeny; Avian Leukosis Virus; Amino Acid Sequence; molekulární evoluce; Disease Susceptibility; Evolution, Molecular; Polymorphism, Genetic; ALV-J; ptačí leukóza; Disease Resistance; Protein Interaction Domains and Motifs; Sodium-Hydrogen Exchangers; kultivované buňky; hostitelská specificita; Avian Leukosis; Animals; Virus Replication; interakce hostitele a patogenu; Quail; antiretroviral resistance; zvířata; sekvence aminokyselin; Cells, Cultured; New World quail; náchylnost k nemoci; Na(+)-H(+) antiport; křepelky a křepelovití; Host Specificity; Amino Acids